MASS MEDIA AS BRANCH OF GOVERNMENT. THE ROLE OF MASS MEDIA AT CONTEMPORARY TIME ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the evolving role of mass media as a branch of government in contemporary times. Traditionally referred to as the "Fourth Estate," mass media plays a critical role in promoting transparency, fostering accountability, and shaping public discourse within democratic societies. The article discusses how mass media acts as a watchdog over governmental power, informs and educates the public, and influences public opinion and policymaking. It examines the challenges and opportunities posed by the digital transformation of media, including issues of misinformation, audience engagement, editorial independence, diversity, and media literacy. By emphasizing the importance of ethical journalism, editorial integrity, and inclusive media practices, the article underscores the essential role of mass media in safeguarding democracy and promoting informed citizenship in the 21st century.